SINTESIS SILIKA MESOPORI TERSULFONASI DARI ABU DAUN BAMBU PETUNG (Dendrocalamus asper) - Precelia, Sari Clara; Subagyono, RR Dirgarini Julia Nurlianti; Saleh, Chairul (JURNAL ATOMIK, 2018)
Research on the synthesis of sulfonated mesoporous Silica from bamboo leaves ash (Dendrocalamus asper) as Heterogeneous Acid Catalyst has been conducted. Bamboo Leaf Ashfish serves as a source of silica for the manufacture of Mesoporous Silica. The research phase consisted of synthesis of MSU-H with surfactant template method, mesoporous silica modification with 3-mercaptopropyl-trimethoxysilane (MPTMS) using post grafting method. The mesoporous silica has a pore volume of 1.03 cm3/g, a surface area of 150 m2/g and a pore diameter of 27.5 nm. The FT-IR spectrum of mesoporous silica before sulfonation shows the presence of Si-O-Si, and Si-OH functional groups while that of Mesoporous silica after sulfonation shows the presence of Si-O-Si, Si-O, Si-OH and –SO3H functional groups.